Reverse engineering code with IDA Pro - Ferguson, Justin; Kaminsky, Dan. (Burlington, MA : Syngress Pub., 2008)
If you want to master the art and science of reverse engineering code with IDA Pro for security R & D or software debugging, this is the book for you. Highly organized and sophisticated criminal entities are constantly developing more complex, obfuscated, and armored viruses, worms, Trojans, and botnets. IDA Pro's interactive interface and programmable development language provide you with complete control over code disassembly and debugging. This is the only book which focuses exclusively on the world's most powerful and popular took for reverse engineering code. *Reverse Engineer REAL Hostile Code To follow along with this chapter, you must download a file called!DANGER!INFECTEDMALWARE!DANGER! ... 'nuff said. *Download the Code! The companion Web site to this book offers up really evil code for you to reverse engineer and really nice code for you to automate tasks with the IDC Scripting Language. *Portable Executable (PE) and Executable and Linking Formats (ELF) Understand the physical layout of PE and ELF files, and analyze the components that are essential to reverse engineering. *Break Hostile Code Armor and Write your own Exploits Understand execution flow, trace functions, recover hard coded passwords, find vulnerable functions, backtrace execution, and craft a buffer overflow. *Master Debugging Debug in IDA Pro, use a debugger while reverse engineering, perform heap and stack access modification, and use other debuggers. *Stop Anti-Reversing Anti-reversing, like reverse engineering or coding in assembly, is an art form. The trick of course is to try to stop the person reversing the application. Find out how! *Track a Protocol through a Binary and Recover its Message Structure Trace execution flow from a read event, determine the structure of a protocol, determine if the protocol has any undocumented messages, and use IDA Pro to determine the functions that process a particular message. *Develop IDA Scripts and Plug-ins Learn the basics of IDA scripting and syntax, and write IDC scripts and plug-ins to automate even the most complex tasks.
Chapter 1: Introduction -- Chapter 2: Assembly and Reverse Engineering Basics -- Chapter 3: Portable Executable and Executable and Linking Formats -- Chapter 4: Walkthroughs One and Two -- Chapter 5: Debugging -- Chapter 6: Anti-Reversing -- Chapter 7: Walkthrough Four -- Chapter 8: Advanced Walkthrough -- Chapter 9: IDA Scripting and Plug-ins -- Index.
Includes index.
Keywords: IDA Pro (Electronic resource); Debugging in computer science -- Computer programs; Computer security -- Computer programs; Reverse engineering -- Computer programs; Electronic books